New Urban Inequalities in The Network Society:An Analysis Based on Manuel Castells' Network Society Theory (Third Sector Social Economic Review, 2025)
This study aims to analyse the new forms of inequality emerging in cities with the digitalisation process, based on Manuel Castells' ‘Network Society’ theory. Castells' theory provides a powerful theoretical framework for understanding the transformation of contemporary social and spatial structures, arguing that in a society where information and communication technologies play a central role, social relations are shaped through digital networks. Rapid developments in information and communication technologies have led to a fundamental change in the forms of social organisation, and the economic, social and administrative effects of this transformation are clearly visible in cities. Digital technologies offer economic development opportunities for cities on the one hand, while reshaping urban service delivery on the other. However, the capacity to benefit from this transformation is directly related to the level of access cities have to digital networks. Cities with a high level of digital integration can benefit more effectively from these opportunities, while cities with inadequate digital infrastructure or limited integration into networks are excluded from the process. This situation deepens structural inequalities between cities. Thus, digitalisation reproduces historically existing spatial inequalities in the digital sphere and causes new forms of urban inequality to emerge in the transition to the information society. In this context, the study re-examines Castells' network society theory in the context of urban inequalities. The aim is to make an original contribution to the literature by examining inequalities based on access to digital networks from a theoretical and critical perspective.
Keywords: Network Society; Manuel Castells; Digitalisation; Urban Inequality